Ultrasound on Erect Penis Improves Plaque Identification in Patients With Peyronie’s Disease - Liu, Yu; Zheng, Dequan; Liu, Xiaolin; Shi, Xiaohong; Shu, Shengchun; Li, Jinbing (Frontiers in Pharmacology, 2019)
Objectives To compare the sensitivity of identification of penile plaques in the erect and flaccid penises by ultrasound in patients with Peyronie’s disease (PD). Materials and Methods A total of 75 PD patients were screened by palpation and ultrasonography for penile lesions in both flaccid and erect penises induced by prostaglandin E1 (PG-1) injection. Results A total of 138 lesions were identified by ultrasound in the erect penises induced by injection of PG-1. However, only 74.6% of the lesions (103) were detectable by the palpation of the flaccid penises, and 84.1% (116) by ultrasound of the flaccid penises. The ultrasound confirmed 99 of the palpated lesions in the flaccid penises. The detection rate of lesions in drug-induced erect penises by ultrasound was significantly higher than those in the flaccid penises by the ultrasound (P < 0.01) or palpation (P < 0.0005) The type of penile lesions identified by ultrasonography included tunical thickening, calcifications, septal fibrosis, and intracavernosal fibrosis. The ratios of these lesions confirmed by ultrasound were 52.6, 33.6, 6.0, and 7.8%, respectively, in the flaccid penises, and 55.8, 28.3, 8.7, and 7.2%, respectively, in the erect penises. Conclusion Drug-induced erection can be used in suspicious PD patients when penile lesion is not identified by palpation or ultrasound in the flaccid penis.